2014
DOI: 10.1099/jmm.0.075291-0
|View full text |Cite
|
Sign up to set email alerts
|

New pharmacological properties of Medicago sativa and Saponaria officinalis saponin-rich fractions addressed to Candida albicans

Abstract: The antifungal activity of the saponin-rich fractions (SFs) from Medicago sativa (aerial parts and roots) and Saponaria officinalis (used as a well-known source of plant saponins) against Candida albicans reference and clinical strains, their yeast-to-hyphal conversion, adhesion, and biofilm formation was investigated. Direct fungicidal/fungistatic properties of the tested phytochemicals used alone, as well as their synergy with azoles (probably resulting from yeast cell wall instability) were demonstrated. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
1
24
0
3
Order By: Relevance
“…To the best of our knowledge, the majority of compounds isolated from Bellis sylvestris, had no precedent in the literature concerning antimicrobial activity, though, in some cases related analogues have been described. Twelve saponins were tested against Candida albicans showing good antifungal activities (Coleman et al, 2010) while triterpenoidc saponins, isolated from Medicago sativa and Saponaria officinalis, showed the ability to limit Candida albicans hyphal growth, contrasting yeast-to-hyphal conversion (Sadowska et al, 2014). Flavonoids activity has also been reported against different yeast species such as Penicillum italicum, Aspergillus flavus and C. albicans, and gram negative bacteria (Cushnie and Lamb, 2005).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…To the best of our knowledge, the majority of compounds isolated from Bellis sylvestris, had no precedent in the literature concerning antimicrobial activity, though, in some cases related analogues have been described. Twelve saponins were tested against Candida albicans showing good antifungal activities (Coleman et al, 2010) while triterpenoidc saponins, isolated from Medicago sativa and Saponaria officinalis, showed the ability to limit Candida albicans hyphal growth, contrasting yeast-to-hyphal conversion (Sadowska et al, 2014). Flavonoids activity has also been reported against different yeast species such as Penicillum italicum, Aspergillus flavus and C. albicans, and gram negative bacteria (Cushnie and Lamb, 2005).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The results of this study, such as the previous study (Chavan et al), show the effectiveness of the anti-bacterial effect of Medicago sativa extract on the bacteria mentioned (10). Various studies have shown that Medicago Sativa has antimicrobial activity against bacteria (24,25). Also, in a similar study carried out by Aliahmadi et al in 2011, the effect of this extract on the elimination of bacteria was confirmed (26).…”
Section: Resultsmentioning
confidence: 99%
“…The test phytochemical could eliminate a good percentage of bacterial biofilm of those selected bacterial strains from the biofilm substratum. Bacoside A could be considered as an effective antimicrobial agent as it gave the MIC value < 400 µg mL -1 (Simões et al 2009 (Khanna et al 2008;Sadowska et al 2014;Ye et al 2015). …”
Section: Discussionmentioning
confidence: 99%